Pharmacological basis of bergapten in gastrointestinal diseases focusing on H+/K+ ATPase and voltage-gated calcium channel inhibition: A toxicological evaluation on vital organs - Aslam, Huma; Khan, Arif-ullah; Qazi, Neelum Gul; Ali, Fawad; Hassan, Syed Shams ul; Bungau, Simona (Frontiers in Pharmacology, 2022)
Aim and objectives: This study aimed to establish a pharmacological basis for evaluating the effects of bergapten (5-methoxypsoralen) in gastrointestinal diseases and assessment of its toxicological profile. Methods: The pharmacokinetic profile was evaluated using the SwissADME tool. AUTODOCK and PyRx were used for evaluating the binding affinities. The obtained results were further investigated for a post-dock analysis using Discovery Studio Visualizer 2016. The Desmond software package was used to conduct molecular dynamic simulations of best bound poses. Bergapten was further investigated for antidiarrheal, anti-secretory, charcoal meal transit time, anti-ulcer, anti-H. pylori activity. Results: Bergapten at a dose of 50, 100, and 200 mg/kg was proved effective in reducing diarrheal secretions, intestinal secretions, and distance moved by charcoal meal. Bergapten at the aforementioned doses acts as a gastroprotective agent in the ethanol-induced ulcer model that can be attributed to its effectiveness against H. pylori. Bergapten shows concentration-dependent relaxation of both spontaneous and K+ (80 mM)-induced contractions in the isolated rabbit jejunum model; the Ca2+ concentration–response curves (CRCs) were shifted to the right showing potentiating effect similar to papaverine. For molecular investigation, the H+/K+ ATPase inhibitory assay indicated inhibition of the pump comparable to omeprazole. Oxidative stress markers GST, GSH, and catalase showed increased expression, whereas the expression of LPO (lipid peroxidation) was reduced. Histopathological examination indicated marked improvement in cellular morphology. ELISA and western blot confirmed the reduction in inflammatory mediator expression. RT-PCR reduced the mRNA expression level of H+/K+ ATPase, confirming inhibition of the pump. The toxicological profile of bergapten was evaluated by an acute toxicity assay and evaluated for behavioral analysis, and the vital organs were used to analyze biochemical, hematological, and histopathological examination. Conclusion: Bergapten at the tested doses proved to be an antioxidant, anti-inflammatory, anti-ulcer, and antidiarrheal agent and relatively safe in acute toxicity assay.